Investigation of Drought Risk Using a Dynamic Optimization Framework in Regional Water Allocation Procedure With Different Streamflow Scenarios - Hong, Xu; Basirialmahjough, Mahdi; He, Yuan; Moudi, Mahdi (Frontiers in Environmental Science, 2022)
Recently, the water supply process has experienced serious challenges, because, with the intensification of drought, the imbalance between available water resources and demand for water in different sectors has led to increased system risk. Therefore, this study proposed an optimal dynamic framework under different scenarios aimed at improving the drought risk of the water supply system. In this sense, given the negative effects of drought on the water supply procedure, the degree of drought risk is analyzed and improved according to system performance parameters. After examining the developed model by initial data collected from a real case study of Hamoun wetland in Iran, the most sensitive parameters were included reliability and vulnerability, which, in this regard, the highest degree of drought risk is related to the agricultural and industrial sectors due to the acquisition of less reliability and greater vulnerability. In addition, given the final output, adaptation measures such as demand governance scheme and weight scenario analysis have been developed in order to investigate the drought risk of the system in more detail.